Research on Integration Scheme of Locomotive-Ground Data Transmission Channel - Li GONG; Bo JIANG; Weiwei ZHANG; Bo LIU (机车电传动)
In view of the current redundancy of railway locomotive-ground transmission tunnel construction, a multi-system locomotive-ground data transmission channel integration scheme based on the Chinese locomotive remote monitoring and diagnosis system (CMD system) was proposed, which strengthened and optimized the security and efficiency of data transmission. Combining the actual requirements, semi-physical simulation test was carried out to verify the data transmission process. The scheme avoided the problem of repeated investment of on-board equipment and mutual interference of vehicle antenna signals, achieved the purpose of reducing communication tariffs and management difficulty, and provided a technical basis for unified application of locomotive data.